Spatial and temporal distribution of insect vectors of Xanthomonas campestris pv. musacearum and their activity across banana cultivars grown in Rwanda. - Rutikanga, A.; Night, G.; Tusiime, Geoffrey; Ocimati, W.; Blomme, Guy (Plant Protection Society of Serbia, 2015)
Insect vectors of Xanthomonas campestris pv musacearum (Xcm) have played a major role in long distance and plant to plant transmission of Xanthomonas wilt of banana (XW). The prevalence of insects has been reported to vary in space and time. Some banana cultivars have also been reported to attract more insect vectors of Xcm than others. The present study was conducted to determine the spatial and temporal distribution of insect vectors of Xcm and assess their activity across banana cultivars grown in Rwanda. The study was carried out in four banana growing areas of Rwanda selected on the basis of their altitude (i.e.Low, Medium and High). The Kivu Lake Border region was selected as a fourth site due to the high prevalence of XW. Insects were sampled in the four annual seasons (short dry, short rainy, long dry and long rainy) and at different times of the day. During sampling of insects, the incidence of XW-male bud infection was also recorded. Collected insects were immediately sorted into taxonomic groups and conserved in vials containing 70% ethanol for further identification to genus and species level. Five insect specimens in each taxon were put aside for the isolation of Xcm on their external body parts. There was a high prevalence of fruit flies, honey bees and other flies (in other families than Drosophilidae and Tephritidae) compared with wasps, ants and beetles. More insects were recorded in the low altitude area and during the long rainy season. These findings correlated with the observed high incidence of XW in the wet seasons. Incidence of floral infections was higher in the low altitudes declining with the increase in altitude, correlating with the decline in insect activity as altitude increased. The activity of insects on banana male buds varied among banana cultivars, with more activity on beer (AAA-East African Highland (EAH) and ABB types) and dessert banana cultivars compared with cooking or mixed use cultivars. Among the cooking types only ‘Injagi’ and its clone sets ‘Barabeshya’ and ‘Incakara’ attracted large insect populations. Banana cultivars ‘Nkazikamwe’ (cooking AAA-EAH), ‘Impura’ (beer AAAEAH) and ‘Ikinyangurube’ (dessert AAA) possessed persistent male bracts and neuter flowers and were less attractive to flower visitors. These cultivars could be promoted in areas prone to insect vector infections. Timely and proper de-budding should be emphasized with special attention during the rainy seasons and for banana cultivars with non-persistent male buds.